Comparative Study of Soil Stabilization Using Ceramic Waste Powder and Glass Waster Powder as Additive - Nanda, Nanda; Imani, Rafki; Mursyid, Muhammad; Pratama, Ade (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2024)
Clay soil is aproblematic soil that high swelling-shrinking properties, expands when given water, and shrinks when dry. One method to improve the clay soil that can be used is soil stabilization using additives or added materials. In this research, the additional materials used are ceramic waste powder (CWP) and glass waste powder (GWP) which will be mixed into clay soil at the location of Koto Baru Nan XX, Padang. The quantities used for each added ingredient are 10%, 15%, 20%, and 25%. The method used is an observation method which aims to analyze the physical and mechanical parameters of the soil before and after adding additional materials. The results of the test show that the plasticity index value using CWP and GWP additives decreased by 85% and 59%, respectively. The increase in UCS value when adding CWP and GWP is almost the same when adding 20%. The OMC value decreased by an average of 40% each with the addition of CWP and GWP. Meanwhile, the increase in MDD value in GWP is greater than the addition of CWP.